Ecofriendly synthesis of silver nanoparticles using metallic solution-based goji berry extract for their antibacterial properties - Abdul Rauf Jamali; Waseem Khan; Salahuddin Khan; Ahmed Ahmed Ibrahim; Kamran Alam (AIP Advances)
Synthesis of silver nanoparticles (Ag-NPs) using green nanotechnology has gained enormous attention due to their extensive range of antibacterial applications such as in the food packaging industry. In this study, Ag-NPs were successfully synthesized using Goji Berry (a fruit of wolfberry) extract. The basic aim of this study is to analyze the antibacterial response of Ag-NPs in gelatin scaffolds. Positively, the reducing agents that are already present in the Goji Berry extract behave as capping and stabilizing agents, so there is no need to add additional constituents from outside. This was then followed by the characterization of samples. The crystallinity of Ag-NPs was determined by X-ray Diffractometer (XRD) that revealed the FCC structure of the sample. The formation of silver particles was confirmed by Ultraviolet–Visible (UV–Vis) spectroscopy. The surface morphology of Ag-NPs was found to be almost spherical, which was determined by a transmission electron microscope and showed spherical particles having an average diameter of 22 nm. Moreover, Fourier transform infrared spectroscopy showed the presence of hydrocarbon groups bonded with Ag-NPs. The antibacterial properties of samples were analyzed by the gram-positive disk diffusion method. It was enhanced when Ag-NPs concentration in gelatin scaffolds increased, thereby producing an 18 mm zone of inhibition.